The House of Pretension: Space and Performance in Miguel Piñero’s Theatre - Irizarry, Roberto (Latin American Theatre Review, 2004)
Nuyorican poet and playwright Miguel Piñero sets his play Short Eyes and his collection Outrageous One-Act Plays in theatrical spaces that highlight confinement as an inescapable reality where identities are dictated by racial and social hierarchies. This emphasis on spatial limitation continues a particular tendency in Puerto Rican island essays and theatre toward representing identities marked by their defensive self-enclosing in domestic spaces. Piñero in turn transforms this isolation by highlighting the marginality of those who experience it and poses a performed element through which solidarity with other ethnic and social groups can be envisioned. By studying this aspect of Piñero’s theatre, Nuyorican drama can be reconnected with island culture in order to transcend a separation of both literary bodies that is common in criticism. (RI)